2014
DOI: 10.1002/pc.23084
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of curing characteristics of carbon fiber/epoxy composites cured with low‐energy electron beam

Abstract: To solve the penetration depth of carbon fiber/epoxy prepreg and irradiation dose uniformity by low-energy E-Beam under 125 keV, the both-side irradiation curing of prepreg was investigated. The results show that there is little thermal effect during the low-energy electron beam irradiation curing process, even though the irradiation dosage reached 300 kGy, only 46.2 C can be tested on the prepreg surface. Due to the low curing temperature, the degree of cure of prepreg was only 61.8% at 300 kGy level of irrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Guasti and Rosi combined low‐energy E‐Beam curing process with wet winding technology and conducted preliminary experimental study . Researchers at Xi'an Jiaotong University further reduced the E‐Beam energy to 125 keV with an improved operability during in situ curing, and proposed the double‐sided irradiation method to obtain a controllable cross‐linking structure along the prepreg thickness direction …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Guasti and Rosi combined low‐energy E‐Beam curing process with wet winding technology and conducted preliminary experimental study . Researchers at Xi'an Jiaotong University further reduced the E‐Beam energy to 125 keV with an improved operability during in situ curing, and proposed the double‐sided irradiation method to obtain a controllable cross‐linking structure along the prepreg thickness direction …”
Section: Introductionmentioning
confidence: 99%
“…In this process, the curing characteristics of irradiated prepregs have been proved strongly related to the interlaminar bonding quality of the laminates, and the curing characteristics can be affected by the E‐Beam irradiation parameters including irradiation energy, irradiation dose, and IDR . For low‐energy E‐Beam curing technology, earlier researches have explored the effects of irradiation energy and irradiation dose on the cuing thickness, curing degree, and postcuring behaviors of the prepregs . However, not much focus has been given to the IDR's influence on the curing characteristics of prepregs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To further reduce the energy of EB and shielding cost, and improve the operability during in‐suit curing, researchers at our laboratory in Xi'an Jiaotong University performed fundamental research on EB curing with energies lower than 150 keV. They have investigated the effect of the EB exposure dose on the curing homogeneity and reported that for low‐energy cured composites, layer‐on‐layer irradiation, and irradiation from two sides could be more efficient to obtain a homogeneous crosslinking structure.…”
Section: Introductionmentioning
confidence: 99%